2014
DOI: 10.1111/plb.12227
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of trehalose biosynthetic pathway to drought stress tolerance of Capparis ovata Desf

Abstract: Trehalose and the trehalose biosynthetic pathway are important contributors and regulators of stress responses in plants. Among recent findings for trehalose and its metabolism, the role of signalling in the regulation of growth and development and its potential for use as a storage energy source can be listed. The xerophytic plant Capparis ovata (caper) is well adapted to drought and high temperature stress in arid and semi-arid regions of the Mediterranean. The contribution of trehalose and the trehalose bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 30 publications
1
31
0
2
Order By: Relevance
“…As such, these fundamental antioxidant and oligosaccharide signaling mechanisms would contribute to biotic and abiotic tolerance in plants. Trehalose is found in organisms such as bacteria, fungi, animals and plants, like Arabidopsis, rice and tobacco, and believed to act as stress protectant molecule (Elbein , Ilhan et al ). These functions have mainly been substituted by sucrose in vascular plants, while recent findings confirmed that the intermediate compound – trehalose‐6‐phosphate – acts as a sensor and controller for available sucrose level in the plants (Lunn et al ).…”
Section: Resultsmentioning
confidence: 99%
“…As such, these fundamental antioxidant and oligosaccharide signaling mechanisms would contribute to biotic and abiotic tolerance in plants. Trehalose is found in organisms such as bacteria, fungi, animals and plants, like Arabidopsis, rice and tobacco, and believed to act as stress protectant molecule (Elbein , Ilhan et al ). These functions have mainly been substituted by sucrose in vascular plants, while recent findings confirmed that the intermediate compound – trehalose‐6‐phosphate – acts as a sensor and controller for available sucrose level in the plants (Lunn et al ).…”
Section: Resultsmentioning
confidence: 99%
“…Both genes are involved in the biosynthesis pathway of trehalose, a non-reducing disaccharide known to be a stress protectant molecule found in several organisms including plants. Generally the constitutive level of trehalose in plant cells is not very high; therefore, it is believed to act as a signaling molecule under stress conditions [74]. In V/2xRL plants, several TPS proteins were identified as bottleneck in the network centrality analysis (Table 1, S2 Table).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, some characteristic sugars that could affect the morphology of leaf were detected, displaying significant species-specific accumulation pattern ( Table 2 ). Trehalose is actively associated with the physiological parameters of plant leaves and limits the growth and development of leaves [ 32 ]. Trehalose has been suggested as a regulatory component in the control of glycolytic flux and in a variety of stress survival strategies [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our result showed that raffinose and trehalose, which are recognized to promote plant resistance to cold conditions, were both largely accumulated in V. minor based on the GC-MS results. Trehalose is reported to help maintain a glassy structure under extreme temperatures and increases the stability of biomolecules [ 32 ]. The changes of raffinose level involve a series of fluctuations of raffinose family oligosaccharides (RFOS) metabolism ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%